Developing Geographical Narratives: Pupils Create Digital Text Adventures with Twine - Veit Maier; Alexandra Budke (European Journal of Investigation in Health, Psychology and Education, 2020)
Applying geographical knowledge in new contexts is a creative and difficult task for school pupils. However, creating text adventures with the open-source tool Twine may be one way to apply geographic knowledge, but there is currently no research that confirms this. We attempted to determine how pupils in small groups constructed text adventures in geography lessons, focused on the topic “Tourism in Myanmar: threat or opportunity”. We recorded the construction processes of 14 pupils audibly, organized into six teams, and analyzed their games. We found that the different text adventure construction activities between the groups had minimal differences. The groups predominantly asked questions and expressed ideas that used meta-conversation for organization and used agreements. These and other text adventure construction activities can help to specify a model of collaborative creativity. In addition, successful groups wrote geographical narratives with adverbs to emphasize the psychological proximity, rhetorical questions and feelings in their stories, and used more words than the others. The results suggest a focus of future research should be on developing a model for integrating geographical narrative skills into geography lessons and intensifying research about collaborative creativity.